PENGARUH PROSES PEMBELAJARAN ONLINE TERHADAP PRESTASI BELAJAR Al-QUR’AN HADITS SISWA KELAS V MI RAUDLATUS SHOLIHIN GEMOLONG SRAGEN TAHUN PELAJARAN 2021/2022 - Arbiyanto, Amlika Hamdan; Yasin, Muhammad (Universitas Nahdlatul Ulama Surakarta, 2024)
The function of online learning is to provide quality and effective services in the teaching and learning process through an open network that can reach more people. This online learning directly involves the role of educators and students in its implementation, and is not limited by space and timeThis paper aims to determine the influence of the online learning process on the learning achievement of the Qur'an Hadith Class V Students of MI Raudlatus Sholihin Gemolong Sragen for the 2021/2022 Academic Year. The type of research used in this study is quantitative. The results showed that the better the online learning process did not affect the better the learning achievement of the Qur'an hadith of grade V students of MI Raudlatus Sholihin Gemolong Sragen for the 2021/2022 academic year.